Engineering Chemistry Vol. 8 - Patrizia Bocchetta; Citlalli Gaona-Tiburcio; Sugianto Sugianto; Karna Wijaya (Trans Tech Publications Ltd, 2024)
The 8th volume of the journal'Engineering Chemistry'includes articles based on research results related to the synthesis of materials used to solve pollutant removal problems. Technologies of pollutant removal, analysis of water and air treatment efficiency, modelling corresponding chemical processes, etc., are also the topics of this journal's issue. This volume will be topical for specialists in the chemistry of environmental protection.